Vertical flower farming – A smart choice - Kumar, P Naveen; S A, Safeena; Aswath, C; G, Senthil Kumaran (Indian Horticulture, 2024)
Vertical farming is a modern agricultural practice of growing crops by stacking the crops vertically in a controlled environment. Vertical farming offers numerous potential benefits, including more efficient use of vertical space, increased planting density, reduced water usage, shorter cultivation time, reduced need for plant protection chemicals, and protection from extreme weather conditions. Vertical farming is considered as an emerging smart sustainable farming solution for urban and peri-urban locations.